A cross sectional study of acute myocardial infarction in young individuals below 40 years and associated risk factors in Mandya institute of medical sciences, Mandya, Karnataka - ., Chandregowda; K., Mahesh; Unnikrishnan, Anagha (International Journal of Advances in Medicine, 2021)
Background: Acute coronary syndrome (ACS) is a potentially life‑threatening condition which is more common in elderly people, and young are relatively protected. Its incidence in young Indians is about 12-16%. Currently, the protective effect on young from coronary artery disease (CAD) is taken away by several risk factors. The aim of this study is to determine the conventional and new emerging risk factors like hyperhomocysteinemia and lipoprotein a (Lp [a]) which are suggested to play an important role in myocardial infarction (MI). Methods: This study was a hospital‑based retrospective cross‑sectional analytical study involving 61 patients aged ≤40years presented with signs and symptoms of ACS confirmed by ECG changes and cardiac enzyme levels admitted in the cardiac ICU from April 2019 to March 2020. Results: Although ACS is a less common entity in young adults aged ≤40 years, smoking was the most common cause of the MI (75%) in young adults. Homocysteine and Lp (a) should be measured in young MI patients. Smoking cessation and prevention of diabetes and hypertension (HTN) should be encouraged. Conclusions: Smoking was the most common cause of the MI (75%) in young adults and is the major modifiable risk factor for MI in very young patients which needs strict prevention. Young patients with CAD were mainly males. There is a need for early detection of a risk factor to prevent the progression of ACS,